Bibliography: Recent Publications in Canadian Labour History [58, Fall 2006] - Lonardo, Michael; Sweeny, Robert C. H. (Labour / Le Travail, 2006)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]
Keywords: BIBLIOGRAPHY (Documentation); WOMEN & war